Original paperTime to failure after definitive therapy for prostate cancer: implications for importance of aggressive local treatment - Taira, Al V.; Merrick, Gregory S.; Butler, Wayne M.; Galbreath, Robert W.; Fiano, Ryan; Wallner, Kent E.; Adamovich, Edward (Journal of Contemporary Brachytherapy, 2013)
Purpose : To explore patterns of time to failure in men receiving high doses of permanent seed brachytherapy with or without external beam radiation therapy as a function of risk status. Material and methods: Two thousand two hundred and thirty four patients were treated with prostate brachytherapy with median follow up of 8.0 years. The population was 35% low risk, 49% intermediate risk, and 16% high risk (NCCN). Median day 0 implant D 90 was 119% and V 100 was 98%. Treatment failure was defined as PSA > 0.40 ng/mL after nadir. Rates of biochemical failure, distant metastases, and prostate cancer death were determined with non-prostate death as a competing risk. Results: For all patients, the 10-year biochemical failure, distant metastases, and cause-specific mortality were 4.4%, 1.4%, and 1.3%, respectively. The biochemical failure rates were 1.3%, 4.8%, and 10.0% for men with low, intermediate, and high risk disease, respectively. Median time to failure was 2.8 years. In men who died from prostate cancer, the median time from treatment failure to death was 4.2 years. Overall, 83% of biochemical failures and 97% of metastases occurred within the first 4 years after treatment. Conclusions : With the dose escalation achieved by high quality brachytherapy dosimetry, even high-risk prostate cancer patients have excellent long term biochemical outcomes. Treatment failures occur early, and one third become metastatic and progress rapidly to prostate cancer death. The low frequency and pattern of failures suggest the presence of micrometastatic disease prior to treatment is rare, even in high risk patients.